Blood and Belief : The Circulation of a Symbol between Jews and Christians - Biale, David, 1949- (Book collections on Project MUSE., 2007)
David Biale traces the continuing, changing and often clashing roles of blood as both both symbol and substance through the entire sweep of Jewish and Christian history, from Biblical times to the present.